Self-assembling peptides as immunomodulatory biomaterials - Hernandez, Andrea; Hartgerink, Jeffrey D.; Young, Simon (Frontiers in Bioengineering and Biotechnology, 2023)
Self-assembling peptides are a type of biomaterial rapidly emerging in the fields of biomedicine and 10 material sciences due to their promise in biocompatibility and effectiveness at controlled release. 11 These self-assembling peptides can form diverse nanostructures in response to molecular 12 interactions, making them versatile materials. Once assembled, the peptides can mimic biological 13 functions and provide a combinatorial delivery of therapeutics such as cytokines and drugs. These 14 self-assembling peptides are showing success in biomedical settings yet face unique challenges that 15 must be addressed to be widely applied in the clinic. Herein, we describe self-assembling peptides' 16 characteristics and current applications in immunomodulatory therapeutics.